Musings on the Architecture and Molecular Arrangement of Polymers in Starch Granules Based on Iodine. Issue 4 (30th July 2013) - Seetharaman, Koushik; Bertoft, Eric
ABSTRACT: The molecular architecture of starch has been the focus of research for over two centuries. However, studies toward understanding the granular architecture of starch have been limited to the crystalline lamellae, and the composition, structure, and organization of polymers in the amorphous background still remain unclear. This essay summarizes some recent results based on novel experiments with iodine vapor–granular starch interactions that occur in the amorphous regions of the granule. In combination with atomic force microscopy, light microscopy, powder spectrophotometry, and X‐ray diffractometry, iodine binding was used to explore the amorphous structures and the architecture of the granule. Results based on heating starch granules in the presence of iodine and their implications are also presented.